Social Media Marketing Platforms and Sales Revenue in Tanzania Telecommunication Company Limited - Pongwe, Leyla Juma; Churk, Josephine (International Review of Management and Marketing, 2024)
Over the past decade, social media platforms such as WhatsApp, Instagram, and Facebook have been used tremendously as a marketing strategy, especially in transforming firms’ interaction with customers. However, few firms have strategized on using social media to expand their geographical reach to customers. This study looks at the effects of social media marketing platforms on sales revenue in Tanzania Telecommunication Company Limited. Specifically, the study assesses the most used social media platform in sales revenue at Tanzania Telecommunication Corporation; and the contribution of the most used social media marketing platform to sales revenue in TTCL. The study is quantitatively designed involving the use of questionnaires in data collection. A cross-sectional study approach was used to gather data from a sample of fifty (50) respondents from Dodoma and Mwanza TTCL commercial regions. Data gathered were analyzed through descriptive and inferential statistics. The results show that Instagram is the social media marketing platform that contributes the most to sales revenue. The study concludes that the use of Instagram promotes sales revenue more than other social media marketing platforms. The study recommends that in order to promote the effective use of technology for sales revenue in public institutions, the government should enact regulations that push these institutions to use social media marketing platforms in advertisements.